A Study of Contextualized-services of Digitalized Museum with Context-Awareness System - Shi, Yunzhen (Advances in Humanities and Contemporary Studies, 2024)
As a new type of service model, contextualized-services has been paid a multi-partite attention both domestically and internationally. Contextualized-services will be the demand of future museum in order to suit the development in a new era. In this study, we mix together the relevant studies to expound relevant concepts and their meanings, and analyze — from three dimensions of user, museum and knowledge — the demand of contextualized-services. Based on the factors of context-data collecting, context-computing, context-model building and context-model assessing, the article analyzes the building process of context-awareness model, and sets up, focusing user as a core, a service framework of digitalized museum’s contextualized-services, that composes of the modules like context-awareness, resources integration, technical support and scene service. The article also discusses the problems involved in contextualized-services and then puts forward relevant solutions. Furthermore, raising up the strategy about perfecting the construction of museum’s experience-available scenes, and by this way, to create a better immersive experience of museum visiting for visitors. The study also discusses the problems involved in contextualized-services and then puts forward relevant solutions. Furthermore, raising up the strategy about perfecting the construction of museum’s experience-available scenes, and by this way, to create a better immersive experience of museum visiting for visitors.